The great basin : a natural prehistory - Grayson, Donald K. (University of California Press, 2011)
"The Great Basin, centering on Nevada and including substantial parts of California, Oregon, and Utah, gets its name from the fact that none of its rivers or streams flow to the sea. This book synthesizes the past 25,000 years of the natural history of this vast region. It explores the extinct animals that lived in the Great Basin during the Ice Age and recounts the rise and fall of the massive Ice Age lakes that existed here. It explains why trees once grew 13' beneath what is now the surface of Lake Tahoe, explores the nearly two dozen Great Basin mountain ranges that once held substantial glaciers, and tells the remarkable story of how pinyon pine came to cover some 17,000,000 acres of the Great Basin in the relatively recent past. These discussions culminate with the impressive history of the prehistoric people of the Great Basin, a history that shows how human societies dealt with nearly 13,000 years of climate change on this often-challenging landscape"--